ANALISIS KEUNTUNGAN DAN NILAI TAMBAH AGRIINDUSTRI MANISAN PALA UD PUTRI DI KOTA BITUNG - Eyverson Ruauw (Sam Ratulangi University, 2012)
This study aims to determine how much profit and value added processing business candied nutmeg. The research was carried out on an industrial UD Women in the Village District Girian Weru Girian Bitung City. The primary data obtained through interviews with the owners daughter UD production period in March 2011. Descriptive analysis of data presented in tabular form, and to know the profit and value-added use profit and loss analysis of value-added analysis. The results showed that profits candied nutmeg on UD daughter of Rp14,983,402.8. Value-added meat processing nutmeg candied nutmeg to Rp45,070 per kilogram of meat nutmeg, with a ratio of 95 percent.Keywords: profit analysis, value added, candied nutme